Metabolic Profile of C-Prenyl Coumarins Using Mass Spectrometry-Based Metabolomics - Yan Cheng (MDPI AG, 2021)
C-prenyl coumarins (C-PYCs) are compounds with similar structures and various bioactivities, which are widely distributed in medicinal plants. Until now, the metabolic characterizations of C-PYCs and the relationship between metabolism and bioactivities remain unclear. In this study, ultra-performance chromatography electrospray ionization quadrupole time-of-flight mass spectrometry-based metabolomics (UPLC-ESI-QTOF-MS) was firstly used to determine the metabolic characterizations of three C-PYCs, including meranzin hydrate (MH), isomeranzin (ISM), and meranzin (MER). In total, 52 metabolites were identified, and all of them were found to be novel metabolites. Among these metabolites, 10 were from MH, 22 were from ISM, and 20 were from MER. The major metabolic pathways of these C-PYCs were hydroxylation, dehydrogenation, demethylation, and conjugation with cysteine, N-acetylcysteine, and glucuronide. The metabolic rate of MH was much lower than ISM and MER, which was only 27.1% in MLM and 8.7% in HLM, respectively. Additionally, recombinant cytochrome P450 (CYP) screening showed that CYP1A1, 2B6, 3A4, and 3A5 were the major metabolic enzymes involved in the formation of metabolites. Further bioactivity assays indicated that all of these three C-PYCs exhibited anti-inflammatory activity, but the effects of ISM and MER were slightly higher than MH, accompanied by a significant decrease in inflammatory cytokines transcription induced by lipopolysaccharide (LPS) in macrophages RAW 264.7. Taken together, the metabolic characterizations of the three C-PYCs suggested that the side chain of the prenyl group may impact the metabolism and biological activity of C-PYCs.